2012
DOI: 10.1308/003588412x13171221591970
|View full text |Cite
|
Sign up to set email alerts
|

The influence of process and patient factors on the recall of consent information in mentally competent patients undergoing surgery for neck of femur fractures

Abstract: INTRODUCTIONInformed consent is an ethical and legal prerequisite for major surgical procedures. Recent literature has identified ‘poor consent’ as a major cause of litigation in trauma cases. We aimed to investigate the patient and process factors that influence consent information recall in mentally competent patients (abbreviated mental test score [AMTS] ≥6) presenting with neck of femur (NOF) fractures.METHODSA prospective study was conducted at a tertiary unit. Fifty NOF patients (cases) and fifty total h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The remaining eight studies on informed consent in adult trauma patients were included in the review for narrative synthesis [40–47] (Table 2). One study was conducted in the United States [40], one in Turkey [42], one in Korea [45], one in Taiwan [46], three in the United Kingdom [41, 43, 44], and one in Ireland [47]. All studies were conducted to evaluate the informed consent process in adult trauma patients.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining eight studies on informed consent in adult trauma patients were included in the review for narrative synthesis [40–47] (Table 2). One study was conducted in the United States [40], one in Turkey [42], one in Korea [45], one in Taiwan [46], three in the United Kingdom [41, 43, 44], and one in Ireland [47]. All studies were conducted to evaluate the informed consent process in adult trauma patients.…”
Section: Resultsmentioning
confidence: 99%
“…8 Additional data in given regarding patients with intellectual disabilities in whom providing information about treatment in written form or with simple visualization of the problem is helpful and increases the effectiveness of consent. 15,16 Also, the use of more clear fonts and adequate spacing help the reader understand the text. 17 A very important aspect of patients' rights described Hocker et al 18 who showed that 31.4% of deaf patients were not informed about their rights and younger age and lower level of education had impact on the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, their questions used dichotomous responses unlike ours that were non-leading open-ended in structure. In another study, only 26% of the test group remembered correctly the surgery undergone the day after the surgery [ 22 ]. Such a very low recall might not be unconnected to the timing of the administration of the test questions.…”
Section: Discussionmentioning
confidence: 99%